The Effect Of Emotional Intelligence And Motivation On Employee Performance With Organizational Commitment As An Intervening Variable In The Office East Binjai District - Sari Humaira; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of emotional intelligence and motivation on employee performance with organizational commitment as an intervening variable in the East Binjai District Office. This study uses a quantitative approach with the Partial Least Squares (PLS) method to test the relationship between variables. Data was collected through a questionnaire distributed to employees of the East Binjai District Office, with a total of 50 respondents. The results showed that emotional intelligence had a positive and significant influence on employee performance with a T-Statistic value of 2.713 > 1.96 and a P-Value of 0.008 < 0.05, but did not have a significant effect on organizational commitment with a T-Statistic value of 0.263 < 1.96 and a P-Value of 0.793 > 0.05. On the other hand, motivation has a positive and significant influence on employee performance with a T-Statistic value of 7.353 > 1.96 and a P-Value of 0.000 < 0.05, as well as on organizational commitment with a T-Statistic value of 8.977 > 1.96 and a P-Value of 0.000 < 0.05. In addition, organizational commitment has a positive and significant influence on employee performance with a T-Statistic value of 7.353 > 1.96 and a P-Value of 0.000 < 0.05. Indirect influence testing showed that organizational commitment did not mediate the relationship between emotional intelligence and employee performance (T-Statistic 0.263 < 1.96, P-Value 0.793 > 0.05). However, organizational commitment proved to be a significant intervening variable in the relationship between employee motivation and performance (T-Statistic 8.977 > 1.96 and P-Value 0.000 < 0.05). This study concludes that motivation is a very important factor in improving employee performance at the East Binjai District Office, both directly and through increasing organizational commitment. Therefore, management is advised to focus on developing programs that can increase organizational motivation and commitment to support the achievement of optimal employee performance.